Teamwork in the time of coronavirus: An MGH experience. Issue 5 (8th October 2020) - Jassar, Arminder S.; Perkins, Katy E.; Sundt, Thoralf M.
Abstract: The global pandemic of coronavirus 2019 (COVID‐19) caused by coronavirus has had a profound impact on the delivery of health care in the United States and globally. Boston was among the earliest hit cities in the United States, and within Boston, the Massachusetts General Hospital provided care for more patients with COVID‐19 than any other hospital in the region. This necessitated a massive reallocation of resources and priorities, with a near doubling of intensive care bed capacity and a halt in all deferrable surgical cases. During this crisis, the Division of Cardiac Surgery responded in a unified manner, dealing honestly with the necessity to reduce Intensive Care Unit resource utilization for the benefit of both the institution and our community by deferring nonemergent cases while also continuing to efficiently care for those patients in urgent or emergent need of surgery. Many of the interventions that we instituted have continued to support teamwork as we adapt to the remarkably fluid changes in resource availability during the recovery phase. We believe that the culture of our division and the structure of our practice facilitated our ability to contribute to the mission of our hospital to support the community in this crisis, and now to its recovery. We describe here the challenge we faced in Boston and some of the details of the structure and function of our division.